2019
DOI: 10.1002/chem.201806230
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bonded Polyrotaxane Cation Structure in Nickel Dithiolate Anion Radical Salts: Ferromagnetic and Semiconducting Behavior Associated with Structural Phase Transition

Abstract: The pseudo‐polyrotaxane structure of [(H‐bpy+)‐ (DB‐24‐crown‐8)]∞ (H‐bpy+ = monoprotonated 4,4‐bipyridinium; DB‐24‐crown‐8 = dibenzo‐24‐crown‐8) has been incorporated into the anion radical salt [Ni(dmit)2]− (dmit2− = 1,3‐dithiole‐2‐thione‐4,5‐dithiolate). (H‐bpy+)(DB‐24‐crown‐8)[Ni(dmit)2]− crystallized as two polymorphs, crystals 1 and 2. Crystal 1 was found to have a lower density and looser packing structure in which H‐bpy+ forms a one‐dimensional hydrogen‐bonding chain that passes though the crown ether r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Previous studies have reported that [24]crown-8 derivatives can include heteroaromatic cations within their cavities. [26][27][28][29] We previously reported the salt (H-bpy + )(DB [24]crown-8)[Ni(dmit) 2 ] À (H-bpy + = monoprotonated 4,4 0 -bipyridine), 30 in which one of the pyridyl rings of H-bpy + is completely included in the DB [24]crown-8 cavity, sandwiched between its phenylene rings. The H-bpy + molecules form one-dimensional (1D) hydrogen-bonded chains and act as pseudo-polyrotaxanes, where one of the two pyridyl rings rotates.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that [24]crown-8 derivatives can include heteroaromatic cations within their cavities. [26][27][28][29] We previously reported the salt (H-bpy + )(DB [24]crown-8)[Ni(dmit) 2 ] À (H-bpy + = monoprotonated 4,4 0 -bipyridine), 30 in which one of the pyridyl rings of H-bpy + is completely included in the DB [24]crown-8 cavity, sandwiched between its phenylene rings. The H-bpy + molecules form one-dimensional (1D) hydrogen-bonded chains and act as pseudo-polyrotaxanes, where one of the two pyridyl rings rotates.…”
Section: Introductionmentioning
confidence: 99%
“…Switchable stimuli-responsive materials, showing compelling richness in terms of potential applications in the fields of data storage, signal processing and sensing, data communication, and optical technologies, have become a popular direction of modern material research. The switching behaviors tuned by externally induced stimuli, such as light, temperature, electric field, and pressure, have brought great impetus for the exploration of dielectric, piezoelectric, pyroelectric, and ferroelectric properties. Among them, the dielectric property manifests collective behavior of polarizable bound charges. The degree of polarizability is described by the real part ε′ of the dielectric constant, ε = ε′ – i ε″, where ε″ is the imaginary part. The ε′ of the switchable dielectric material displays an obvious anomaly between high and low dielectric states around T c , which are mainly due to the dynamic or motional transformations between disordered and ordered states and the displacement in molecules or ions. Such changes usually accompany with the structural phase transition and often provoke symmetry breaking with the temperature decreasing. Consequently, it is an effective way to find novel responsive switchable compounds composed of temperature-sensitive flexible components to enrich the family of dielectric materials and promote the process of application in smart devices.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical results are in accordance with the formula n- n-Bu 4 N[Pd((R)-α-MBAdto)(quinoxdt)] (5). Na (9.2 mg, 0.4 mmol) was added to 15 mL of MeOH; the resulting solution was added dropwise to a stirred suspension of [1,3]dithiolo [5,6][1,4]dithiino [2,3-b]quinoxalin-2-one (59.1 mg, 0.18 mmol) in 50 mL of 50% MeOH/50% CHCl 3 . The mixture was stirred for 30 min at room temperature to give a reddish brown dithiolate solution.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The interest in metal dithiolene chemistry in basic science , and in various fields of materials chemistry has been fueled by the growing attention to heteroleptic derivatives with potential application in dye-sensitized solar cells or in second-order nonlinear optics (NLO). , By well-established engineering, these complexes can be obtained as planar and low-energy-gap molecules consisting of a π-acceptor (A) and a π-donor (D) ligand connected by a d 8 metal in a square-planar coordination, where the metal acts as a suitable π-bridge for the D–A charge transfer (CT) transition. Several other classes of complexes, where a d 8 metal (mostly platinum) connects a variety of suitably engineered D–A ligands, are of interest for their NLO and photoemissive properties as well as in photocatalysis .…”
Section: Introductionmentioning
confidence: 99%